Condenser Optimization of Heat Pipe - Radovan Nosek; Stanislav Gavlas; Richard Lenhard; Veroslav Sedlak; Havard Mollerhagen Arvesen (Communications, 2014)
Construction of heat exchanger assembly has important role for efficient operation of energy systems. Within this assembly a heat pipe is utilized for heat transfer. The condensation part of the heat pipe is situated on top of the heating zone. The device placed in the heating zone is condenser which is used for efficient heat transfer from one medium to another. The thermal oil is used as cooling medium in the condenser. This paper analyzes the effect of different operation conditions of thermal oil to thermal performance. From the collected results it is obvious that the larger mass flow and higher temperature cause better thermal performance and lower pressure drop.